Transparansi yang Tertunda: Analisis Keterbukaan Informasi Publik pada Website PPID Komisi Pemilihan Umum Kota Jambi - Sherly Rosmadita; Dimas Subekti; Suci Rahmadani (Yayasan Literasi Sains Indonesia, 2026)
This research aims to explain in depth about public information disclosure implemented by the Jambi City General Election Commission (KPU). The method used in this research is qualitative, with a case study approach to reveal comprehensive information. The data collection techniques used include direct interviews with relevant parties and analysis of relevant documentation to get an accurate picture. The results showed that public information disclosure at the Jambi City KPU had not been implemented properly. The timeliness indicator did not update information on the Jambi City KPU PPID website for the last three years. In the completeness indicator, that the completeness of information on the PPID website of the Jambi City KPU there is information that is not available in the absence of important data such as the latest financial reports and information on the 2024 elections and regional election. As a result, the website is not reliable as the main source of information for the community. Then on the accuracy indicator, the Jambi City KPU showed inaccuracies, mainly because the PPID website did not update data regularly.